2018
DOI: 10.1098/rsos.172360
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the inclusion of a mixed Psychrotrophic bacteria strain for sewage treatment in constructed wetland in winter seasons

Abstract: Constructed wetlands (CWs) have been used globally in wastewater treatment for years. CWs represent an efficient ecological system which is both energy-saving and low in investment for construction and operational cost. In addition, CWs also have the advantage of being easy to operate and maintain. However, the operation of CWs at northern latitudes (both mid and high) is sometimes quite demanding, due to the inhibitory effect of low temperatures that often occur in winter. To evaluate the wastewater treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 25 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…The experiment proved that the dissolved oxygen concentration in wastewater treatment had better control precision and effect than the traditional controller [ 3 ]. Tang et al explored the treatment strategy for constructed wetland wastewater, explored the use of ecological control systems to improve the environmental protection of wastewater, and used the effects of mixed strains to comprehensively control the growth of strains to achieve environmental protection of wetlands [ 4 ]. Kühr et al explored how current wastewater treatment plants could use engineering nanoparticles to improve the effect of wastewater treatment.…”
Section: Related Workmentioning
confidence: 99%
“…The experiment proved that the dissolved oxygen concentration in wastewater treatment had better control precision and effect than the traditional controller [ 3 ]. Tang et al explored the treatment strategy for constructed wetland wastewater, explored the use of ecological control systems to improve the environmental protection of wastewater, and used the effects of mixed strains to comprehensively control the growth of strains to achieve environmental protection of wetlands [ 4 ]. Kühr et al explored how current wastewater treatment plants could use engineering nanoparticles to improve the effect of wastewater treatment.…”
Section: Related Workmentioning
confidence: 99%
“…Species such as Phragmites australis and Typha orientalis are commonly used in VSFCW for an improved performance in the warmer environment; however, in the low-temperature season, these species would deteriorate or wither [17]. The activities of most microorganisms in VSFCW are weakened under low-temperature conditions and only a few microorganisms are able to maintain normal life activities [18]. Consequently, the treatment ability of VSFCW in the low-temperature season is poor.…”
Section: Introductionmentioning
confidence: 99%
“…The composition and structure of microbial community are the main factors affected the e uent quality of constructed wetlands (Ibekwe, Grieve, and Lyon 2003;Kaushal, Wani, and Patil 2019;Hamdan, Salam, and Saikaly 2019). However, physical conditions such as low temperature affect the growth and activity of plants and population structure and metabolism of microorganisms in the CWs wastewater treatment process (Adams, Crump, and Kling 2010;Aromokeye et al 2018;Zeng et al 2019).The number of microorganisms and the metabolic e ciency of exogenous substances would be reduced under low temperature, so it is hard to form dominant micro ora through natural selection, resulting in poor sewage treatment, or even substandard (Tang et al 2018). Therefore, how to ensure the treatment effect of CWs under low temperature has become an urgent problem to be solved.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of microorganisms will be lost, making it di cult to control its long-term treatment effect. As a result, it is found that the function of two or more microbial strains to combine the dominant strains has a better synergistic effect than a single strain (Tang et al 2018;Ying et al 2010). In previous research, Ying et al (Ying et al 2010)explored the ammonia nitrogen removal rates of the three cold-resistant strains into the constructed wetland system in cold areas to remove the winter wastewater.…”
Section: Introductionmentioning
confidence: 99%